The Relationship Between Workload, Locus of Control, and Self Efficacy with Performance: A Study on Employees at PT Petrokopindo Cipta Selaras Factory - Fadilah, Maulana Azhar; Firdaus, Vera (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to determine and analyze the partial and simultaneous effects of workload, locus of control, and self-efficacy on employee performance at PT Petrokopindo Cipta Selaras, Sidoarjo. The type of research used is explanatory research with a population of 100 employees. The sampling technique applied is total sampling, so that the number of respondents reaches 100 people. Data analysis was carried out using multiple regression, including the t test and F test. The results showed that all variables had a significant effect on employee performance. Workload has a positive effect, especially when the tasks assigned are in accordance with the capabilities of employees, and can even have a positive impact if they exceed capacity. Locus of control plays an important role, where employees who are able to control themselves and think positively tend to be more successful in completing tasks. Self-efficacy is also shown to have a significant influence, with employees who have high self-confidence being able to solve the problems and tasks given. Overall, this study concludes that encouraging clear work goals, as well as providing adequate support and resources, will create a comfortable work environment and can improve employee performance.